2018
DOI: 10.14444/5090
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Respiratory Complications Following Lumbar Spine Surgery

Abstract: Background: The purpose of this study is to assess the incidence, risk factors for, and types of respiratory complications occurring in patients undergoing lumbar spine surgery.Methods: Patients undergoing various lumbar spine surgeries from 2007 to 2014 were identified using the PearlDiver patient record database from the nationwide insurance provider Humana Inc. Patient records were analyzed using International Classification of Diseases, Ninth Revision codes and Current Procedural Terminology codes to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…It would seem reasonable to assume that smoking is associated with significant pulmonary complications. Several authors have indeed found a correlation between smoking and postoperative pulmonary complications in patients undergoing lumbar fusions[ 9 ] and in adults undergoing spinal deformity surgery. [ 34 ] This relationship, however, has not been confirmed by all authors: Bohl et al could not confirm the association between smoking and postoperative pneumonia and Jules-Elysee et al did not find an association between smoking and the development of pulmonary radiographic abnormalities in patients undergoing anterior-posterior thoracic lumbar fusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would seem reasonable to assume that smoking is associated with significant pulmonary complications. Several authors have indeed found a correlation between smoking and postoperative pulmonary complications in patients undergoing lumbar fusions[ 9 ] and in adults undergoing spinal deformity surgery. [ 34 ] This relationship, however, has not been confirmed by all authors: Bohl et al could not confirm the association between smoking and postoperative pneumonia and Jules-Elysee et al did not find an association between smoking and the development of pulmonary radiographic abnormalities in patients undergoing anterior-posterior thoracic lumbar fusions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 ] The results of prior studies on the association between cigarette smoking and postoperative complications have been conflicting. While some of these studies revealed increased 30-day readmission rates, SSI,[ 5 6 7 ] perioperative transfusion risks,[ 8 ] deep venous thrombosis (DVT),[ 5 ] and pulmonary complications,[ 9 ] others have not. [ 3 10 11 12 13 14 15 ] There are few studies explicitly addressing perioperative complications in smokers following thoracolumbar fusion surgeries, and the studies that do exist are most commonly derived from a small cohort of patients from a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of atelectasis and other postoperative pulmonary complications, which are enhanced by general anesthesia, significantly decreases with epidural anesthesia and analgesia ( 14 ). Decreased functional residual capacity, forced vital capacity and prone positioning lead to atelectasis ( 15 ).…”
Section: Regional Anesthesia In Spinal Surgerymentioning
confidence: 99%
“…Decreased functional residual capacity, forced vital capacity and prone positioning lead to atelectasis ( 15 ). Studies reported that the incidence of atelectasis in postoperative period is up to 50%, followed by infiltrate, lobar collapse and pneumonia in patients who received general anesthesia ( 14 , 15 ).…”
Section: Regional Anesthesia In Spinal Surgerymentioning
confidence: 99%
“…Postoperative pulmonary complications (PPCs) including pneumonia, atelectasis, respiratory failure, and exacerbations of underlying chronic lung disease, result in prolonged hospital stays (Murgai et al, 2018). About one in five patients with PPCs die within 30 days of PPC development (Miskovic & Lumb, 2017; Norris et al, 2019; Ramachandran et al, 2011; Smetana, 2009).…”
Section: Introductionmentioning
confidence: 99%